Strategic Trade Policy and Merger Profitability - Steffen Huck; Kai A. Konrad (Center for Economic Studies and ifo Institute (CESifo), 2003)
We study the profitability incentives of merger and the endogenous industry structure in a strategic trade policy environment. Merger changes the strategic trade policy equlilibrium. We show that merger can be profitable and welfare enhancing here, even though it would not be profitable in a laissez-faire economy. A key element is the change in the governments. incentives to give subsidies to their local firms. National merger induces more strategic trade policy, whereas international merger does not.
Keywords: 330; merger incentives; strategic trade policy